Additive manufactured polymeric 3D scaffolds with tailored surface topography influence mesenchymal stromal cells activity. (24th May 2016) - Neves, Sara C; Mota, Carlos; Longoni, Alessia; Barrias, Cristina C; Granja, Pedro L; Moroni, Lorenzo
Abstract: Additive manufactured three-dimensional (3D) scaffolds with tailored surface topography constitute a clear advantage in tissue regeneration strategies to steer cell behavior. 3D fibrous scaffolds of poly(ethylene oxide terephthalate)/poly(butylene terephthalate) block copolymer presenting different fiber surface features were successfully fabricated by additive manufacturing combined with wet-spinning, in a single step, without any post-processing. The optimization of the processing parameters, mainly driven by different solvent/non-solvent combinations, led to four distinct scaffold types, with average surface roughness values ranging from 0.071 ± 0.012 μ m to 1.950 ± 0.553 μ m, average pore sizes in the x - and y -axis between 351.1 ± 33.6 μ m and 396.1 ± 32.3 μ m, in the z -axis between 36.5 ± 5.3 μ m and 70.7 ± 8.8 μ m, average fiber diameters between 69.4 ± 6.1 μ m and 99.0 ± 9.4 μ m, and porosity values ranging from 60.2 ± 0.8% to 71.7 ± 2.6%. Human mesenchymal stromal cells (hMSCs) cultured on these scaffolds adhered, proliferated, and produced endogenous extracellular matrix. The effect of surface roughness and topography on hMSCs differentiation was more evident for cells seeded at lower density, where the percentage of cells in direct contact with the surface was higher compared to more densely seeded scaffolds. Under osteogenic conditions, lower surface roughness values (0.227 ± 0.035 μ m) had a synergistic effect on hMSCs behavior, while chondrogenesis was favored on rougher surfaces (1.950 ± 0.553 μ m).